(x+1x) = 13−−√,(x+1x) = 13,\left( {x + \frac{1}{x}} \right){\text{ = }}\sqrt {13} {\text{,}} then the value of (x3+1x3)" role="presentation">(x3+1x3)(x3+1x3)\left( {{x^3} + \frac{1}{{{x^3}}}} \right) is = ?" /> (x+1x) = 13−−√,(x+1x) = 13,\left( {x + \frac{1}{x}} \right){\text{ = }}\sqrt {13} {\text{,}} then the value of (x3+1x3)" role="presentation">(x3+1x3)(x3+1x3)\left( {{x^3} + \frac{1}{{{x^3}}}} \right) is = ?" /> (x+1x) = 13−−√,(x+1x) = 13,\left( {x + \frac{1}{x}} \right){\text{ = }}\sqrt {13} {\text{,}} then the value of (x3+1x3)" role="presentation">(x3+1x3)(x3+1x3)\left( {{x^3} + \frac{1}{{{x^3}}}} \right) is = ?" />
Post your Comments